The Abuse of the Right to Information Outside of Board in Corporation and the Limitations to its Exercise - Leturia, Eduardo (2019)
In Peru, article 52-A of the General Corporation Law incorporated the shareholders’ right to information outside of the General Shareholders Board for companies. In said article, this right is limited by two aspects: (i) that it must be requested by shareholders representing no less than five percent (5%) of the paid capital and (ii) that the required information must not compromise reserved facts or matters whose disclosure may damage the company. Although the aforementioned law does not explicitly indicate it, another restriction is that said right cannot be exercised in an abusive manner. This paper discusses the limitations to the shareholders’ right to information outside the General Shareholders Board and the abuse of said right, questioning whether it needs to be audited or if it compels the administration to prepare information required by the shareholders.